Immunohistochemical study of phyllodes tumor of the breast - Yashar, Genghis; Basheska, Neli; Kubelka, Katerina; Zografski, George (Springer, 1999)
Phyllodes tumor ('PT) is a rare, fibroepithelial breast neoplasm with unpredictable prognostic and controversial therapeutic aspects. Aims: The aim of this retrospective study is to evaluate Ki-67 and CD34 antigen expression, as well as estrogen (ER) and progesterone receptor (PgR) status in stromal cells, as additional diagnostic criteria in assessing different types of PT. Methods: Routinely processed, formalin-fixed and paraffin-embedded surgical specimens from 47 cases of PT were stained by immunoperoxidase technique using Ki-67, CD34, ER and PgR monoclonal antibodies. On the basis of histopathological criteria proposed by Azzopardi, 6 malignant, 12 borderline and 29 benign PT have been evaluated. The mean size of the tumour was 9.4 cm (range 2.8-20 era). During the follow-up period (mean 50, range 2-127 months), recurrences were observed in 8 patients (17%). Results: The proliferating index determined by Ki-67 antigen expression was significantly different between histologically benign PT (19%), borderline PT (25%) and malignant PT (50%). There was a difference of the human progenitor cell CD34 antigen expression in malignant PT (50%), borderline PT (50%) and benign PT (30%). As expected, the stromal cells in various types of PT were mostly ER negative and PgR positive. Conclusions: Our preliminary results suggest that CD34 positivity and high proliferative index of Ki-67 antigen in stromal cells are more frequently associated with high grade PT. Therefore, the immunohistochemical features could provide better discrimination between different PT types. The prognostic implications of these observations should be evaluated in additional studies.
Keywords: breast; phyllodes tumor; histopathology; immunohistochemistry; Ki-67; prognosis